Faulkner, Welty, Wright: a Mississippi confluence - Trefzer, Annette; Watson, Jay; Thomas, James G. Jr. (Faulkner and Yoknapatawpha Series, 2024)
An engaging, diverse collection that considers together a trio of Mississippi literary giants.